Chronic Binge Alcohol Consumption Does Not Diminish Effectiveness of Continuous Antiretroviral Suppression of Viral Load in Simian Immunodeficiency Virus‐Infected Macaques. (September 2014) - Molina, Patricia E.; Amedee, Angela M.; Veazey, Ron; Dufour, Jason; Volaufova, Julia; Bagby, Gregory J.; Nelson, Steve
<x xml:space="preserve">Abstract</x> Background Alcohol use disorders (AUDs) are a frequent comorbidity in a large percentage of people living with HIV/AIDS (PLWHA). PLWHA with comorbid AUDs are consistently found to perform poorly at most levels of the HIV treatment cascade, resulting in a higher likelihood of virologic nonsuppression. This has been partly attributed to lower rates of persistence with and adherence to antiretroviral therapies (ART). Focus groups of in‐care PLWHA identify the need to suspend ART on drinking days because of the potential for toxicity and/or lack of therapeutic effectiveness. The aim of this study was to examine whether chronic binge alcohol (CBA) consumption decreases the effectiveness of uninterrupted ART, specifically that of nucleoside reverse‐transcriptase inhibitors (NRTI) tenofovir and emtricitabine in suppressing viral replication, or results in drug toxicity in simian immunodeficiency virus (SIV)‐infected rhesus macaques. Methods Daily CBA or isocaloric sucrose (SUC) administration was initiated 3 months prior to intrarectal SIVmac251 inoculation and continued throughout the study period. ART was initiated 2.5 months after SIV infection and continued through the study period. Results CBA administration did not prevent or delay the ART‐mediated reduction in viral load. Following ART, circulating levels of total protein and creatinine were significantly higher than baseline values in both SUC‐ and CBA‐treated animals, but still within a normal range. No evidence of ART toxicity was observed in either CBA‐ or SUC‐administered macaques. Conclusions These findings indicate that CBA does not attenuate effectiveness of NRTI suppression of viral load, nor does it appear to interact with NRTI to produce toxicity during the initial 2 months of treatment. We conclude that while efforts to reduce AUD in PLWHA should be a priority, counseling on the importance of adherence to ART even on drinking days should also be promoted.